Research on the improvement of CPI basic classification index compilation method in digital economy - Zhixiu Du; Jinzhu Du (PLoS ONE, 2025)
Information and communication technology (ICT) products are the core of the digital economy, and their classified price index plays an important role in the compilation of CPI index. This paper starts from the characteristics of ICT products that have a fast update rate and do not necessarily meet the unit substitution elasticity between products, and improves the traditional product price index model by considering the mismatch item processing and product substitution elasticity and chain drift factors to construct the Hedonic-SV-RYGEKS price index model in this paper. Using the weekly data of Jingdong mobile phone price on whale staff platform and the monthly data of notebook computer on magic mirror insight platform, after processing, a total of 1586 sets of mobile phone data and 136 sets of notebook computer data are obtained. By writing SPSS macro program and python program, the weekly price index of mobile phone and the monthly price index of notebook computer are calculated, and the ring price index and fixed base price index of mobile phone and notebook computer are compiled respectively. The chain ring price index based on model calculation is compared with the fixed base price index to investigate the rationality of the model. The results show that: Firstly, based on the principle of the quality adjustment model, the characteristic variables that can reflect the characteristics of the product are selected, and a Hedonic quality adjustment model is established between them and the product price. Through the actual data test, the model is suitable for fitting the price of mismatched products. Secondly, from the perspective of reflecting the elasticity of substitution of products, the evaluation criteria of the price index, and the adjustment of product quality, this paper constructs the Hedonic-SV-RYGEKS price index based on the Hedonic model and SV index, which avoids the incomparability of samples caused by the low matching degree of inter-temporal samples, and effectively inhibits the chain drift of chain price index caused by the rapid update of products. Finally, it is hoped that the research content of this paper can provide a reference for improving and innovating the processing method of mismatched projects in the compilation of price index.